1990
DOI: 10.1111/j.1469-8137.1990.tb00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of radish to multiple stresses

Abstract: SUMMARYExperiments were conducted to determine the impact of nitrogen and ozone (O3) stress on the growth of domestic radish Raphanus sativus L. cv. Cherry Belle. Plants were grown in field chambers with sub-, optimal and supraoptimal levels of nitrogenous fertilizer. Chamber air was either charcoal-filtered, or supplemented with one of two levels of O3. The highest O3 treatment resulted in significant reduction in weight of hypocotyls and roots while elevated nitrogen treatments resulted in increased weight o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
1
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 19 publications
3
24
1
1
Order By: Relevance
“…Such a tend has been documented previously (Paakonen et al, 1995) but the converse, an increase in sensitivity under a highnutrient regime, is more frequently reported (Cowling & Koziol, 1982 ;Pell et al, 1990 ;Tjoelker & Luxmoore, 1991). The difference might be due to the relative degree of nutrient limitation.…”
Section: mentioning
confidence: 66%
See 1 more Smart Citation
“…Such a tend has been documented previously (Paakonen et al, 1995) but the converse, an increase in sensitivity under a highnutrient regime, is more frequently reported (Cowling & Koziol, 1982 ;Pell et al, 1990 ;Tjoelker & Luxmoore, 1991). The difference might be due to the relative degree of nutrient limitation.…”
Section: mentioning
confidence: 66%
“…Older reports are reviewed by Cowling & Koziol (1982). More recently, a number of studies have shown that plants grown under a high-nutrient regime are more sensitive to ozone (Pell et al, 1990 ;Tjoelker & Luxmoore, 1991), but in contrast, Paakonen, Holopainen & Karenlampi (1995) reported greater sensitivity of birch trees under nutrient deficiency. Heagle (1979) found greater sensitivity to ozone in plants supplied with moderate amounts of nutrients than in those with a very low or high supply.…”
mentioning
confidence: 99%
“…Several groups, however, have also examined the impact of O3/N interactions on plant growth (Adedipe & Hofstra, 1973;Pell et al, 1990). We examined the interaction between O3 and N on growth of the cultivated radish, Raphanus sativus L. Cherry Belle (Pell et al, 1990). In these studies plants grown with higher rates of N appeared to sustain greater reductions in biomass under O3 stress.…”
Section: Introductionmentioning
confidence: 99%
“…Viroflay plants grown either at optimum or relatively large rates of N, respectively, exhibited greater foliar symptoms in response to O., (Brewer, Buillemet & Creveling, 1961;Leone, Brennan & Daines, 1966). Several groups, however, have also examined the impact of O3/N interactions on plant growth (Adedipe & Hofstra, 1973;Pell et al, 1990). We examined the interaction between O3 and N on growth of the cultivated radish, Raphanus sativus L. Cherry Belle (Pell et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Soil type has also been shown to influence plant response to O.j (Reich et al, 1986;Stroo et al, 1988) and might be a major factor contributing to differential sensitivity to O3. Soil nutrient limitations can intensify the physiological effects of O3 while unlimited nutrient availability might reduce plant response to O3 (Pell et al, 1990;Gorissen, Joosten & Jansen, 199U;Greitner, Pel! & Winner, 1994;Paakkonen & Holopainen, 1995).…”
mentioning
confidence: 99%